Postal networks : actors in the social and eeconomic development of the Caribbean region : regional development plan 2017-2020 (Universal Postal Union BerneCH, 2017)
Provides a brief description of some of the key projects that the UPU intends to implement in the region during the 2017-2020 cycle.